A Calculation Method of Angular Contact Ball Bearing Contact Stiffness Considering Lubrication Effect - Fengxia Lu; Zhiqiang Zhao; Wenbin Pan; Heyun Bao (Jixie chuandong)
A dynamics model of high-speed angular contact ball bearings under the lubrication condition is established， in the calculation of contact deformation and contact stiffness between ball bearing and inner/outer ring， the influence of lubricating oil entrainment and squeeze during high-speed rotation is considered. Through the coupling iteration of contact angle and contact stiffness， the calculation method of axial and radial stiffness of high-speed angular contact ball bearings considering lubrication effect is obtained. The results show that after considering the lubrication effect， the contact angle between the ball and the inner/outer ring decreases， and the axial/radial stiffness of the bearing increases. The increase in the axial load increases the axial/radial stiffness， and the lower the axial load， the more obvious the effect of lubricating oil. The increase in the radial load makes the axial stiffness increase and the radial stiffness decrease. As the number of rollers increases，the axial/radial stiffness increases，and the effect of lubricating oil is more obvious; Compared with 4019 lubricant， 4106 lubricant increases bearing axial/radial stiffness. The axial/radial stiffness of ceramic ball bearings is greater than steel ball bearings， and has an approximately linear relationship with the speed.